Lei de cotas e representação: a seleção de candidatas para a Câmara Municipal de Goiânia nas eleições de 2020 - Moraes, Ana Carolina de Brito (2021)
The present investigation focuses specifically on the results of the Quota Law for the insertion of women in the city of Goiânia, analyzing the process of selection of candidates for the Municipality of Goiânia in the 2020 elections and the profile of elected candidates . The topic is relevant, since most studies in this area take place at the federal level. The general objective is to analyze the proportionally smaller participation of women in Brazilian political positions, with a focus on Goiânia and on the effectiveness of the Quota Law. Thus, the process of applying the Quota Law in the selection of women in political parties for candidates for councilor in the Municipality of Goiânia was investigated. The methodology used instruments such as analysis of electoral legislation, decision-making mechanisms adopted by political parties, electoral data provided by the Superior Electoral Court (TSE) and interviews with candidates, elected or not, and party leaders. In this sense, the data and the interviews allowed us to understand that as much as the parties comply with the legislation foreseen in relation to gender quotas, it is not enough, there is still a long way to go. The interviews yielded very interesting results, as they approached the backstage of electoral campaigns and how each party operates. It was found that there is no internal preparation in the parties concerned with the formation and political preparation of women, aiming at really competitive candidacies.